2002
DOI: 10.1074/jbc.m202527200
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor (FGF)-23 Inhibits Renal Phosphate Reabsorption by Activation of the Mitogen-activated Protein Kinase Pathway

Abstract: The homeostasis of the plasma phosphate level is essential for many biological processes including skeletal mineralization. The reabsorption of phosphate in the kidney is a major determinant of the plasma levels of phosphate. Phosphatonin is a hormone-like factor that specifically inhibits phosphate uptake in renal proximal epithelial cells. Recent studies on tumor-induced osteomalacia suggested that phosphatonin was potentially identical to fibroblast growth factor (FGF)-23. However, as purified recombinant F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
3
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 21 publications
8
150
3
4
Order By: Relevance
“…Cleavage of the intact 30 kDa-secreted protein results in two smaller fragments of ~18 kDa (amino fragment) and 12 kDa (carboxy fragment) of yet unknown function. Although various studies have shown that FGF-23 can exert certain activities through binding to the known receptors for other members of the FGF family (13,14), the search for a novel receptor that specifically mediates the actions of FGF-23 is ongoing. Genetic modifications of FGF-23 in animals have shown phenotypes similar to those of human diseases.…”
mentioning
confidence: 99%
“…Cleavage of the intact 30 kDa-secreted protein results in two smaller fragments of ~18 kDa (amino fragment) and 12 kDa (carboxy fragment) of yet unknown function. Although various studies have shown that FGF-23 can exert certain activities through binding to the known receptors for other members of the FGF family (13,14), the search for a novel receptor that specifically mediates the actions of FGF-23 is ongoing. Genetic modifications of FGF-23 in animals have shown phenotypes similar to those of human diseases.…”
mentioning
confidence: 99%
“…FGF23 contains a consensus binding domain for FGFRs and several studies have suggested that FGF23 may bind and activate signaling through one or more FGFRs [31][32][33]. Recent in vivo genetic manipulation studies suggest that both FGF23 and KLOTHO act through a common signaling pathway [30] and that KLOTHO facilitates FGF23 binding to an FGFR [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant FGF-23 either had no effect (72) or inhibited (38,68) Na/P i cotransport in OK cells. Moreover, the inhibition that was observed was either prevented (68) or dependent (38) on the presence of heparin in the incubation medium. In the latter study, it was demonstrated that FGF-23 bound to FGF receptor 3c and that inhibition of Na/P i cotransport was mediated by a MAPK signaling pathway (38).…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 95%
“…Studies in opossum kidney (OK) cells demonstrated that the extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) pathway also participates in PTH-induced signaling (37). In addition, FGF-23, a factor contributing to renal P i wasting in autosomal dominant hypophosphatemic rickets and oncogenic hypophosphatemic osteomalacia (see below), inhibits type IIa-mediated Na/P i cotransport in OK cells via activation of MAPK (38). Moreover, it was recently documented in isolated perfused cortical slices that the different signaling pathways (PK-A, PK-C, PK-G) converge on the ERK/MAPK pathway to internalize type IIa protein (D. Bacic, C. Wagner, J. Biber, H. Murer; submitted).…”
Section: The Type Iia Na/p I Cotransporter As a Target For Physiologimentioning
confidence: 99%